Exploratory Evaluation of Rhythm Control by Dronedarone in Combination With Low-Dose Rivaroxaban, Warfarin, Antiplatelet, or None of the Antithrombotic Therapy in High-Risk Patients With Non-Permanent Atrial Fibrillation: A Retrospective Cohort Study. (December 2021) - Lin, Po-Lin; Chiou, Wei-Ru; Su, Min-I; Huang, Chun-Che; Liao, Feng-Ching; Liu, Lawrence Yu-Min; Chuang, Jen-Yu; Chen, Chun-Yen; Tsai, Cheng-Ting; Kuo, Jen-Yuan; Yang, Ten-Fang; Wu, Yih-Jer; et al.
The emerging data supports rhythm control to prevent major adverse cardiac events (MACE) in high-risk patients with atrial fibrillation (AF). Limited data demonstrated rivaroxaban 10 mg combining dronedarone seemed feasible. This study aimed at investigating clinical events in a dronedarone-treated cohort. This exploratory, retrospective chart review was conducted in nonpermanent AF patients receiving dronedarone for ≥ 3 months between 2009/1 and 2016/2. In Taiwan, dronedarone's labeled indication was strict to age ≥ 70 or 65 to 70 years with either hypertension, diabetes, prior stroke, or left atrium >50 mm. We divided all into 4 groups using antithrombotic strategies to evaluate the safety, effectiveness, and MACE endpoints. A total of 689 patients (mean CHA2 DS2 -VASc score 3.8 ± 1.4) were analyzed: rivaroxaban 10 mg (n = 93, 13.5%), warfarin (n = 89, 12.9%), antiplatelet (n = 331, 48.0%), and none (n = 176, 25.5%). During the follow-up period (mean 946 ± 493.8 days), the rivaroxaban group did not report any stroke or thromboembolism (ishcmeic stroke rate: antiplatelet [0.6%], none [1.1%]; hemorrahgic stroke rate: warfarin [2.2%]; thromboembolism rate: warfarin [2.2%]). There was no significant difference in safety, effectiveness, and MACE endpoints between groups. Also, >104 weeks of dronedarone use was the independent predictor for MACE after adjusting the strategy and other covariates (hazard ratio 0.14 [95% confidence interval 0.04-0.44], P = .001). Our findings warrant concomitant rivaroxaban 10 mg and dronedarone for further investigation. Regardless of antithrombotic strategies, a more extended persistence of dronedarone was associated with fewer MACE.